A three-pronged attack to investigate the electronic structure of a family of ferromagnetic Fe 4 Ln 2 cyclic coordination clusters: a combined magnetic susceptibility, high-field/high-frequency electron paramagnetic resonance, and 57 Fe Mössbauer study - Schmidt, Sebastian F. M.; Koo, Changhyun; Park, Jaena; Heermann, Dieter W.; Klingeler, Rüdiger (Inorganic chemistry, 2017)
We present the synthesis, structure, magnetic properties, as well as the Mössbauer and electron paramagnetic resonance studies of a ring-shaped [FeIII4LnIII2(Htea)4(μ-N3)4(N3)3(piv)3] (Ln = Y 1, Gd 2, Tb 3, Dy 4, Ho 5, Er, 6) coordination cluster. The Dy, Tb, and Ho analogues show blocking of the magnetization at low temperatures without applied fields. The anisotropy of the 3d ion and the exchange interaction between 3d and 4f ions in Fe4Ln2 complexes are unambiguously determined by high-field/high-frequency electron paramagnetic resonance measurements at low temperature. Ferromagnetic exchange interaction JFe-Ln is found which decreases upon variation of the Ln ions to larger atomic numbers. This dependence is similar to the behavior shown in the effective barrier values of complexes 3-5. Further information about the anisotropy of the Ln3+ ions was gathered with 57Fe Mössbauer spectroscopy, and the combination of these methods provides detailed information regarding the electronic structure of these complexes.